The awareness and acceptance of Roundtable on Sustainable Palm Oil (RSPO) among smallholders in oil palm plantation at Felcra Nasaruddin, Perak / Sofia Azman - Azman, Sofia (Faculty of Plantation and Agrotechnology, 2017)
The Roundtable on Sustainable Palm Oil (RSPO) is an organization that was established to developed the practices for sustainable palm oil production such as economic, environmental and social requirements of producing sustainable palm oil. However, the smallholders are lack of the awareness about the RSPO and there are almost no studies focussing on the process of smallholder inclusion. This study is to examine the factors affecting the RSPO awareness and the acceptance of RSPO among smallholders in Bota, Perak on economic, social and environment. A total number of 86 respondents have been chosen randomly to answer the closed-ended questionnaire. The data collected has been analysed by using Statistical Package for Social Science (SPSS) to determine descriptive analysis, demography study, correlation and regression. The findings on the smallholders indicated that all elements of RSPO awareness and acceptance have a positive linear correlation. From the regression analysis showed that only 24.1% of variation in RSPO awareness is explained by economic and environment. The findings also showed that only 28% of variation in RSPO acceptance is explained by economic and social. The overall conclusion shows that many smallholders are not aware to the RSPO. However it is still perceived that a number of additional measurable variables could be adopted to assist in properly quantifying sustainability.